Variational Formulation and A Priori Estimates for the Galerkin Method for a Fractional Diffusion Equation - Lima, M. E. de S.; Oliveira, E. C. de; Viana, A. da C. (Trends in Computational and Applied Mathematics, 2022)
In this work we obtain a variational formulation and a priori estimates for approximate solutions of a problem involving fractional diffusion equations.